Validity and Practicality of Interactive Multimedia Based on PBL Assisted Quizzes on Environmental Pollution to Improve Learning Motivation and Digital Literacy - Yovita Yovita; Mery Berlian; Rian Vebrianto; Musa Thahir; Dilva Hardila (JINoP (Jurnal Inovasi Pembelajaran), 2025)
A digitally literate person can use technology strategically to search for and evaluate information, as well as to connect and collaborate with others. In digital learning environments, students are required to develop a set of essential skills known as digital literacy. These skills are crucial for ensuring that learning can take place effectively in the digital era and for helping students become independent, critical thinkers. This study aims to develop effective Problem-Based Learning (PBL) Interactive Multimedia to support students' digital literacy. The type of research used is Research and Development (R&D), applying the Dick and Carey instructional design model. This model comprises ten systematic steps, ranging from identifying instructional goals to conducting summative evaluations. The result of this study is a PBL-based interactive multimedia product that has been validated by experts and tested by users. Based on the validation process, the multimedia product received a score of 88%, which falls into the "Very Valid" category. In addition, the practicality test showed a score of 86%, indicating that the product is "Practical" and easy to use for both teachers and students. Therefore, the developed multimedia is considered suitable and effective for use as an interactive learning tool that supports problem-based learning in today’s digital classroom environment.